Performance Evaluation of Various Phase Change Materials for Thermal Energy Storage of A Solar Cooker via Numerical Simulation - Tarwidi, Dede; Murdiansyah, Danang Triantoro; Ginanjar, Narwan (International Journal of Renewable Energy Development, 2016)
In this paper, thermal performance of various phase change materials (PCMs) used as thermal energy storage in a solar cooker has been investigated numerically. Heat conduction equations in cylindrical domain are used to model heat transfer of the PCMs. Mathematical model of phase change problem in the PCM storage encompasses heat conduction equations in solid and liquid region separated by moving solid-liquid interface. The phase change problem is solved by reformulating heat conduction equations with emergence of moving boundary into an enthalpy equation. Numerical solution of the enthalpy equation is obtained by implementing Godunov method and verified by analytical solution of one-dimensional case. Stability condition of the numerical scheme is also discussed. Thermal performance of various PCMs is evaluated via the stored energy and temperature history. The simulation results show that phase change material with the best thermal performance during the first 2.5 hours of energy extraction is shown by erythritol. Moreover, magnesium chloride hexahydrate can maintain temperature of the PCM storage in the range of 110-116.7°C for more than 4 hours while magnesium nitrate hexahydrate is effective only for one hour with the PCM storage temperature around 121-128°C. Among the PCMs that have been tested, it is only erythritol that can cook 10 kg of the loaded water until it reaches 100°C for about 3.5 hours.Article History: Received June 22nd 2016; Received in revised form August 26th 2016; Accepted Sept 1st 2016; Available onlineHow to Cite This Article: Tarwidi, D., Murdiansyah, D.T, Ginanja, N. (2016) Performance Evaluation of Various Phase Change Materials for Thermal Energy Storage of A Solar Cooker via Numerical Simulation. Int. Journal of Renewable Energy Development, 5(3), 199-210.http://dx.doi.org/10.14710/ijred.5.3.199-210